Advancing the Risk Analysis for Alien Taxa (RAAT) framework - Sabrina Kumschick; Llewellyn C. Foxcroft; John R. U. Wilson (NeoBiota)
The Risk Analysis for Alien Taxa (RAAT) framework was developed to collate scientific information and interpret it in the context of South African regulations on biological invasions. Feedback from the past four years has shown RAAT to be a valuable tool for making evidence-based, transparent recommendations, but one that can be improved. We describe the changes made in creating RAAT v2.0. We note several issues that we suspect will apply to many similar processes, namely the need to i) clarify descriptions; ii) remove superfluous questions; and iii) add questions to fully justify recommendations. We also stress what RAAT v2.0 does not do—the framework does not summarise management best practices nor does it, or South Africa’s regulatory lists, provide sufficient information to prioritise management resources. We strongly recommend that explicit feedback mechanisms are set up to ensure that similar such frameworks can be improved over time.